The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.6061/clinics/2016(03)05
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical ventilation in patients in the intensive care unit of a general university hospital in southern Brazil: an epidemiological study

Abstract: OBJECTIVES:To determine the characteristics, the frequency and the mortality rates of patients needing mechanical ventilation and to identify the risk factors associated with mortality in the intensive care unit (ICU) of a general university hospital in southern Brazil.METHOD:Prospective cohort study in patients admitted to the ICU who needed mechanical ventilation for at least 24 hours between March 2004 and April 2007.RESULTS:A total of 1,115 patients admitted to the ICU needed mechanical ventilation. The mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
56
6
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(83 citation statements)
references
References 34 publications
15
56
6
6
Order By: Relevance
“…Also, the patients of heart failure and COPD need more extended hospitalization and lower death rate in ICU when compared with sepsis patient. These findings have described in previous studies [27] [28], found that one-third of 119 COPD patients who admitted to ICU mechanically ventilated for a median duration of 3 days and nine days in the hospital.…”
Section: Discussionsupporting
confidence: 83%
“…Also, the patients of heart failure and COPD need more extended hospitalization and lower death rate in ICU when compared with sepsis patient. These findings have described in previous studies [27] [28], found that one-third of 119 COPD patients who admitted to ICU mechanically ventilated for a median duration of 3 days and nine days in the hospital.…”
Section: Discussionsupporting
confidence: 83%
“…The possible explanation for this association could be related that mechanical ventilators initiated for the patients with respiratory failure, unable to protect the airway and hemodynamic instability. Furthermore, patients who need intubation and mechanical ventilator more vulnerable for ventilator associated pneumonia and other nosocomial infections (23,24). Our study reveled that patients who presented with abnormal mental status were more likely to die than conscious patients (AOR: 2.741, P<0.001).…”
Section: Discussionmentioning
confidence: 99%
“…is prospective study was performed in a 24-bed medical ICU at Chang Gung Memorial Hospital, Taiwan. e inclusion criteria for this study were as follows: (1). patients who had been mechanically ventilated for more than 24 h with PSV levels of 8 cmH 2 O, PEEP ≤8 cmH 2 O, and FiO 2 ≤40%.…”
Section: Methodsmentioning
confidence: 99%
“…For patients with acute respiratory failure, mechanical ventilation (MV) is the cornerstone of management. Patients admitted to the intensive care unit (ICU) who require MV are expected to have higher mortality rates than those who do not require respiratory support [1]. e application of the mechanical ventilator is crucial for patients with critical illness, especially during the weaning process.…”
Section: Introductionmentioning
confidence: 99%